Hydrological soil properties control tree regrowth after forest disturbance in the forest steppe of central Mongolia - Schneider, Florian; Klinge, Michael; Brodthuhn, Jannik; Peplau, Tino; Sauer, Daniela (SOIL, 2021)
The central Mongolian forest steppe forms a transition between different ecozones and is as such particularly sensitive to environmental changes. It is commonly affected by disturbances such as logging and forest fires. Intensified drought events aggravate stress on the trees that are anyway at their drier limit in the forest steppe. Climate change increases evapotranspiration and reduces the distribution of discontinuous permafrost, which leads to drier soil conditions. The motivation for this study came about through our previous observation that forest stands show great differences with respect to their recovery after disturbance by fire or logging. Sometimes, no regrowth of trees takes place at all. As water availability is the main limiting factor of forest growth in this region, we hypothesised that differences in soil hydrology control the forest recovery pattern. To test this hypothesis, we analysed soil properties under forests, predominantly consisting of Siberian larch (Larix sibirica Ledeb.), in the forest steppe of the northern Khangai Mountains, central Mongolia. We distinguished the following four vegetation categories: (1) near-natural forest (FOR), (2) steppe close to the forest (STE), (3) disturbed forest with regrowth of trees (DWIR), and (4) disturbed forest showing no regrowth of trees (DNOR). A total of 54 soil profiles were described in the field and sampled for soil chemical, physical, and hydrological analysis. We found a significant difference in soil texture between soils under DWIR and DNOR. Sand generally dominated the soil texture, but soils under DWIR had more silt and clay compared to soils under DNOR. Soil pF curves showed that soils under DWIR had higher plant-available field capacity in their uppermost parts than soils under DNOR. In addition, hydraulic conductivity tended to be higher in the uppermost horizons of soils under DWIR compared to their counterparts under DNOR. Chemical properties of the soils under DWIR and DNOR showed no significant differences. We conclude that ...